Workshop Green Parenting Era Digital: Mengembangkan Kecerdasan Naturalistik dan Karakter Peduli Lingkungan Anak melalui Budidaya Sayuran - Titin Nurhidayati; M. Nafiur Rofiq; Rofiatul Hosna; Akhsani Ulvatun Ni’mah (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2026)
Parenting challenges in the digital era are increasingly characterized by nature-deficit disorder, resulting from children's excessive dependence on digital devices, which has led to declining naturalistic intelligence and reduced environmental awareness. This community service program aimed to empower members of the Family Welfare Movement (PKK) as al-madrasatul ula (the child's first and primary educational environment) to foster children's naturalistic intelligence and environmental stewardship through the Green Parenting approach. The program employed the Asset-Based Community Development (ABCD) approach by utilizing local physical assets, particularly home gardens, and human assets through participatory workshops on cultivating horticultural vegetables, including chili peppers, tomatoes, and eggplants. The implementation consisted of four stages—discovery, dream, design, and define—to optimize nature-based psychological support for children. The results showed an 85% increase in participants' understanding of strategies for stimulating multiple intelligences and improving their technical skills in organic farming. The program successfully integrated horticultural cultivation with Islamic Educational Psychology, transforming home gardens into character-building environments that instill the values of shabr (patience), amanah (responsibility), and tawhid rububiyyah (recognition of Allah's Lordship). The program's sustainability was strengthened through the establishment of a PKK self-learning community that continues to replicate Green Parenting as a sustainable parenting model. Keywords: Green Parenting, Digital Era, Naturalistic Intelligence, PKK Mothers, Vegetable Cultivation Abstrak: Tantangan pola asuh di era digital ditandai oleh fenomena nature-deficit disorder akibat tingginya ketergantungan anak pada gawai, yang berdampak pada menurunnya kecerdasan naturalistik dan kepedulian terhadap lingkungan. Kegiatan pengabdian masyarakat ini bertujuan untuk memberdayakan ibu-ibu PKK sebagai al-madrasatul ula dalam mengembangkan kecerdasan naturalistik dan karakter peduli lingkungan pada anak melalui konsep Green Parenting. Metode yang digunakan adalah pendekatan Asset-Based Community Development (ABCD) dengan memanfaatkan aset fisik berupa pekarangan rumah dan aset manusia melalui lokakarya partisipatif budidaya sayuran hortikultura, meliputi cabai, tomat, dan terong. Tahapan pelaksanaan mencakup discovery, dream, design, dan define untuk mengoptimalkan dukungan psikologis anak berbasis alam. Hasil kegiatan menunjukkan peningkatan pemahaman peserta sebesar 85% mengenai strategi stimulasi kecerdasan majemuk dan keterampilan pertanian organik. Program ini berhasil mengintegrasikan budidaya hortikultura dengan Psikologi Pendidikan Islam sehingga pekarangan rumah berfungsi sebagai laboratorium pembentukan karakter yang menanamkan nilai shabr, amanah, dan tauhid rububiyah. Keberlanjutan program diperkuat melalui pembentukan komunitas belajar mandiri PKK yang mereplikasi praktik Green Parenting sebagai model pengasuhan yang berkelanjutan. Kata kunci: Green Parenting, Era Digital, Kecerdasan Naturalistik, Ibu PKK, Budidaya Sayuran.